Um estudo sobre o uso de módulos core em testes automatizados de aplicações Node.js - Oliveira Filho, Julio Cesar dos Santos (Universidade Federal de São Carlos, 2024)
With the continuous advancement of web applications, understanding their behaviors and key operations is indispensable for improving the technologies used. This study focuses on the analysis of asynchronous functions in test cases of a set of real applications using Node.js. Specifically, the core modules of Node.js were studied, exploring their functions and asynchronous patterns. Initially, Node.js projects were selected for analysis based on defined criteria. Subsequently, the projects' tests were executed by a prototype, and their asynchronous functions were documented in JSON records. Finally, a tool for reading these records was built, aiming to analyze and generate new data for this work, transcribed in the form of spreadsheets and charts. From a large amount of generated data, four research questions related to the use of core modules, the proportion of each core module in relation to the total asynchronous functions, the most frequent asynchronous patterns, and the most used functions by modules were answered. In conclusion, a certain pattern of use of asynchronous functions was observed, with some modules being preferred over others. Moreover, a significant disparity between the two most used asynchronous patterns was identified, with the first showing considerably greater use than the second.
A study on the usage of core modules in automated tests of Node.js applications
Keywords: Funções assíncronas; Testes automatizados; JavaScript; Node.js; Módulos core; Async functions; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO